2005
DOI: 10.1089/lap.2005.15.325
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Resection of Appendiceal Mucinous Cystadenoma

Abstract: Mucinous cystadenoma is a rare lesion of the vermiform appendix and is seldom diagnosed before surgery, although radiologic and ultrasonographic findings have been reported. We present the case of a 65-year-old female with rheumatoid arthritis who presented with general malaise, poor appetite, fever, and right upper and lower quadrant pain of about one week's duration. Abdominal sonography and computed tomography revealed an 8 x 4 x 3 cm cystic lesion of the appendix. Laparoscopic evaluation confirmed this fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
(23 reference statements)
0
20
0
2
Order By: Relevance
“…5,10,14,24 Some surgeons consider that the operation can be performed using a laparoscopic method by adhering to safety rules, especially when removing the mucocele from the abdomen and an endobag must be used. 1,25,26 An algorithm for the selection of the type of surgery has been furnished by Dhage, Ivatury and Sugarbaker.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,14,24 Some surgeons consider that the operation can be performed using a laparoscopic method by adhering to safety rules, especially when removing the mucocele from the abdomen and an endobag must be used. 1,25,26 An algorithm for the selection of the type of surgery has been furnished by Dhage, Ivatury and Sugarbaker.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies do not recommend laparoscopic method in the surgical treatment of mucoceles due to the risk of rupture (6,8), Chiu reported that laparoscopic appendectomy is appropriate when performed carefully (12). In the second case, we preferred to perform laparoscopic appendectomy and close follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,17,26 Some surgeons consider that the operation can be performed using a laparoscopic method by adhering to safety rules, especially when removing the mucocele from the abdomen and an endobag must be used. 1,27,28 An algorithm for the selection of the type of surgery has been furnished by Dhage-Ivatury and Sugarbaker. 13 It envisages several factors: (1) whether or not a mucocele is perforated; (2) whether the base of the appendix (margins of resection) is involved in the process; and (3) whether there are positive lymph nodes of mesoappendix and ileocolic.…”
Section: Discussionmentioning
confidence: 99%